Spatial heterogeneity of the planktonic protistan community in a semi-closed eutrophic bay, China. (25th November 2017) - Du, Ping; Jiang, Zhi B; Wang, Yong M; Qian, Peng; Hu, Han J; Liao, Yi B; Zhou, Kong L; Zeng, Jiang N; Chen, Quan Z; Shou, Lu; Zhang, De M
Abstract: We examined the planktonic protistan community in Xiangshan Bay during spring 2015 using 18S rDNA sequencing. We found significant spatial heterogeneity in α-diversity, β-diversity (Bray–Curtis and Jaccard indices) and the relative abundance of dominant taxa. The spatial heterogeneity of the protistan community was due more to variation in species (operational taxonomic units) than abundance, and the spatial variation in species was dominated by variation in rare biota. Salinity was the most important driver of spatial heterogeneity in the total community and the abundant subcommunity, but environmental factors could not explain the variation in the rare subcommunity. For α-diversity, spatial heterogeneity was mainly associated with the rare biota; α-diversity was positively correlated with water mass complexity but negatively correlated with temperature and nutrients. Of the dominant protistan phyla, the more abundant Cryptophyta, Chlorophyta and Haptophyta were correlated with lower salinity and higher nutrient concentrations, while the more abundant mixotrophs (e.g. Dinoflagellata and Protalveolata) were associated with lower nutrient concentration. Our study suggests that rare taxa are important for preserving the spatial heterogeneity of the protistan community, whose structural variation might be influenced by biotic interactions.